2009
DOI: 10.1116/1.3110027
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional molecular dynamics simulation of nanostructure for reciprocating nanomachining process

Abstract: Three-dimensional molecular dynamics simulations are conducted to investigate the effect of reciprocating nanomachining process on the subsurface damaged layers, surface integrity, cutting force, stress variation of subsurface, and changes of energy and defects in the workpiece. Results show that there is no obvious shear zone ahead the tool during nanomachining. Dislocation nucleations are near the free surface ahead the tool and the interface of the tool and the workpiece and propagate in the surface and dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…49 Simulations of nanomachining of copper showed that dislocations nucleate near the surface of the workpiece and emit into the crystal. 48 When machining was conducted at previously scratched regions with high defect densities, the cutting load was decreased. 48 Also, atomistic simulation of nanoindentation of Cu, [56][57][58] Ni 59 and Mo 60 at grain boundaries predicted that lower contact stresses were required for plasticity than required in the interior of perfect crystals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Simulations of nanomachining of copper showed that dislocations nucleate near the surface of the workpiece and emit into the crystal. 48 When machining was conducted at previously scratched regions with high defect densities, the cutting load was decreased. 48 Also, atomistic simulation of nanoindentation of Cu, [56][57][58] Ni 59 and Mo 60 at grain boundaries predicted that lower contact stresses were required for plasticity than required in the interior of perfect crystals.…”
Section: Discussionmentioning
confidence: 99%
“…These regions of high crystallographic defect density may be plastically deformed by abrasive particles sliding on the surface of the wafer, leaving an even higher defect density in the copper, as predicted with MD simulation. 48 The crystallographic defects lower the shear strength of copper because they facilitate activation of the dislocation source 29,49,50 or function as sites for heterogeneous nucleation of dislocations. 50 MD simulations predicted that vacancies in otherwise perfect Fe crystals 51 and Ni cyrstals 30,52 reduced the stress required for the onset of plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been reported on MD simulations of nanoindentaion and nanoscratching. The effects of several parameters such as crystal orientation [41,45,46], indenter shape and orientation [33,39,40,44], penetration or scratching depth [37,42,47,48], scratching speed [47,48], feed (on nanoscratching) [34,35], and temperature [25,45,49] have been investigated on different types of bulk and thin film materials. In addition, mechanical properties including Young's modulus, friction coefficient and hardness of materials have also been reported [26,42].…”
Section: Introductionmentioning
confidence: 99%
“…According to the general WKB approximation and subsequent transmission models based thereon, low φ and high β typically manifest as high J max . In practice, however, for non‐classical materials, such as nanowires and nanotubes, the intimate mechanisms which augment the emission are not yet fully understood . This study focuses on the effect of changing φ across a diverse material range in an attempt to rationalize the importance of emitter work function in comparison to the degree of perturbation in emitter geometries.…”
mentioning
confidence: 99%